The legal and ethical aspects of spiritual care in medical practices / Ramizah Wan Muhammad - Wan Muhammad, Ramizah (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2024)
Spiritual care is important to ensure that the physical and mental health of a person is protected. Spiritual care in the context of Muslims is very much associated with iman and amal soleh of a person. A Muslim is required to perform Ibadah, reciting the Quran and doa as prescribed in the Quran and Sunnah as part of protecting his mind, soul and physical from any harmful or negative elements. The duty to take care of the soul and spiritual part of a Muslim is crucial especially if he is suffering from any terminal illness that could affect his mental health and possibly his physical health will be more affected. This paper is to discuss the ethical values of spiritual care in the context of Islamic religion and the legal and practical aspects of as what has been practiced in Malaysia.